Computational exploration of borophane-supported single transition metal atoms as potential oxygen reduction and evolution electrocatalysts. Issue 32 (3rd August 2018) - Singh, Yashpal; Back, Seoin; Jung, Yousung
Abstract : Surface activation of 2D borophane for oxygen reduction and evolution reactions is demonstrated with the help of substitutional transition metal doping. Abstract : Novel monolayer-boron (borophene) is a recent addition to the family of 2D materials. In particular, full surface hydrogenation of triangular borophene (borophane (BH)) to passivate empty p orbitals in boron is identified as producing a new stable 2D material that possesses direction-dependent Dirac cones similar to graphene. By a series of density functional theory (DFT) computations, we investigated the potential of single transition metal atoms supported on borophane with vacancies (the TM–BH system) as an efficient ORR/OER electrocatalyst for applications in renewable energy technologies. In TM–BH systems, the coupling of d-orbitals of the TM dopant with the p-orbitals of surrounding boron atoms results in an increase in the density of states near the Fermi-level generating active sites to facilitate the ORR/OER via an efficient four-electron transfer mechanism. Among the considered TM–BH systems, Fe–BH and Rh–BH were found to be promising ORR electrocatalysts with overpotentials ( η ORR ) of 0.43 V and 0.47 V, respectively, whereas, for the OER, Rh–BH with 0.24 V has the smallest η OER value followed by Co–BH (0.37 V), under the equilibrium electrode potential. These η ORR and η OER values indicate higher activities than the current most active ORR (Pt(111) (0.63 V)) and OER (rutile-type RuO2 (0.37 V)) electrocatalysts.